Structural Modification of TiO2 Nanorod Films with an Influence on the Photovoltaic Efficiency of a Dye-Sensitized Solar Cell (DSSC) - Meng, Lijian (2014)
TiO2 nanorod films have been deposited on ITO substrates by dc reactive magnetron sputtering technique. The structures of these nanorod films were modified by the variation of the oxygen pressure during the sputtering process. Although all these TiO2 nanorod films deposited at different oxygen pressures show an anatase structure, the orientation of the nanorod films varies with the oxygen pressure. Only a very weak (101) diffraction peak can be observed for the TiO2 nanorod film prepared at low oxygen pressure. However, as the oxygen pressure is increased, the (220) diffraction peak appears and the intensity of this diffraction peak is increased with the oxygen pressure. The results of the SEM show that these TiO2 nanorods are perpendicular to the ITO substrate. At low oxygen pressure, these sputtered TiO2 nanorods stick together and have a dense structure. As the oxygen pressure is increased, these sputtered TiO2 nanorods get separated gradually and have a porous structure. The optical transmittance of these TiO2 nanorod films has been measured and then fitted by OJL model. The porosities of the TiO2 nanorod films have been calculated. The TiO2 nanorod film prepared at high oxygen pressure shows a high porosity. The dye-sensitized solar cells (DSSCs) have been assembled using these TiO2 nanorod films prepared at diferente oxygen pressures as photoelectrode. The optimum performance was achieved for the DSSC using the TiO2 nanorod film with the highest (220) diffraction peak and the highest porosity.